Deaths from injury in children and employment status in family: analysis of trends in class specific death rates. Issue 7559 (7th July 2006) - Edwards, Phil; Roberts, Ian; Green, Judith; Lutchmun, Suzanne
Abstract: Objective To examine socioeconomic inequalities in rates of death from injury in children in England and Wales. Design Analysis of rates of death from injury in children by the eight class version of the National Statistics Socio-Economic Classification (NS-SEC) and by the registrar general's social classification. Setting England and Wales during periods of four years around the 1981, 1991, and 2001 censuses. Subjects Children aged 0-15 years. Main outcome measures Death rates from injury and poisoning. Results Rates of death from injury in children fell from 11.1 deaths (95% confidence interval 10.8 to 11.5 deaths) per 100 000 children per year around the 1981 census to 4.0 deaths (3.8 to 4.2 deaths) per 100 000 children per year around the 2001 census. Socioeconomic inequalities remain: the death rate from all external causes for children of parents classified as never having worked or as long term unemployed (NS-SEC 8) was 13.1 (10.3 to 16.5) times that for children in NS-SEC 1(higher managerial/professional occupations). For deaths as pedestrians the rate in NS-SEC 8 was 20.6 (10.6 to 39.9) times higher than in NS-SEC 1; for deaths as cyclists it was 27.5 (6.4 to 118.2) times higher; for deaths due to fires it was 37.7 (11.6 to 121.9) times higher; and for deaths of undetermined intent it was 32.6 (15.8 to 67.2) times higher. Conclusions Overall rates of death from injury and poisoning in children have fallen in England and Wales over the past 20 years, except for rates in children in families in which no adult is in paid employment. Serious inequalities in injury death rates remain, particularly for pedestrians, cyclists, house fires, and deaths of undetermined intent.